Synthesis of Unsymmetrical Squaramides as Allosteric GSK‐3β Inhibitors Promoting β‐Catenin‐Mediated Transcription of TCF/LEF in Retinal Pigment Epithelial Cells. (27th October 2022) - Carullo, Gabriele; Bottoni, Laura; Pasquini, Silvia; Papa, Alessandro; Contri, Chiara; Brogi, Simone; Calderone, Vincenzo; Orlandini, Maurizio; Gemma, Sandra; Varani, Katia; Butini, Stefania; Galvagni, Federico; et al.
Abstract: The glycogen synthase kinase 3β (GSK‐3β) is a ubiquitous enzyme that is a validated target for the development of potential therapeutics useful in several diseases including retinal degeneration. Aiming at developing an innovative class of allosteric inhibitors of GSK‐3β potentially useful for retinal degeneration, we explored the class of squaramides. The developed compounds (6 a –l ) were obtained through a nontoxic one‐pot synthetic protocol, which employs low‐cost goods and avoids any purification step. Ethanol was used as the reaction solvent, simultaneously allowing the pure reaction products′ recovery (by precipitation). Out of this set of squaramides, 6 j stood out, from computational and enzymatic converging data, as an ATP non‐competitive inhibitor of GSK‐3β of micromolar potency. When engaged in cellular studies using retinal pigment epithelial cells (ARPE‐19) transfected with a luciferase reporter gene under the control of T‐cell factor/lymphoid enhancer factor (TCF/LEF) binding sites, 6 j was able to dose‐dependently induce β‐catenin nuclear accumulation, as shown by the increased luciferase activity at a concentration of 2.5 μM. Abstract : A green approach to obtain unsymmetrical squaramides, new GSK‐3β inhibitors, able to promote β‐catenin‐mediated TCF‐LEF gene transcription is reported. From computational and enzymatic converging data, compound 6 j stood out as an ATP non‐competitive inhibitor of GSK‐3β with micromolar potency. In studies using retinal pigment epithelial (ARPE‐19) cells transfected with a luciferase reporter gene under the control of T‐cell factor/lymphoid enhancer factor (TCF/LEF) binding sites, 6 j was able to dose‐dependently induce β‐catenin nuclear accumulation, as shown by the increased luciferase activity at a concentration of 2.5 μM.